Cassava Starch-Based Films Reinforced with Clay Minerals - Passos, Elthon Ferreira; Marangoni, Rafael; Zatta, Leandro (Orbital: The Electronic Journal of Chemistry, 2018)
This paper presents the obtaining and characterization of starch-based polymeric films with the addition of kaolinite, montmorillonite and a commercial clay as filler, glycerol was used as plasticizer. The materials were characterized through X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, thermogravimetry, mechanical properties, colorimetry and water solubility. It was generally found that the addition of the clay minerals to the polymer matrices altered the evaluated properties of the materials. The films containing the clay minerals presented lower temperatures of occurrence of the thermal events, greater capacity of elongation, lower rupture tension and greater resistance to water solubility. The film containing the commercial clay stands out for presenting red coloration, due to the presence of iron contents in the clay composition. The films synthesized from starch with the addition of glycerol and natural origin clay minerals obtained in this work demonstrated interesting properties for technological applications. DOI: http://dx.doi.org/10.17807/orbital.v10i7.1171